Pulse duration measurements of grazing-incidence-pumped high repetition rate Ni-like Ag and Cd transient soft x-ray lasers - Chang, Zenghu, author; Gilbertson, S., author; Shakya, Mahendra Man, author; Rocca, Jorge J., author; Luther, B. M., author; Wang, Y., author; Berrill, M., author; Larotonda, M. A., author; Optical Society of America, publisher (Colorado State University. Libraries, 2006)
We have measured the pulse duration of gain-saturated 13.9 nm Ni-like Ag and 13.2 nm Ni-like Cd transient collisional lasers excited by grazing-incidence-pumping for several pumping conditions. High-resolution streak-camera measurements yielded FWHM pulse durations close to 5 ps for both lasers under optimum pumping conditions. The very high brightness and short pulse duration of these new high repetition tabletop soft x-ray lasers make them an attractive source for dynamic applications.